Power, Culture, and Harmony in the Javanese Political Ethos: An Anthropological and Cultural Analysis in Relavance with the Surinamese Diaspora - Giorgio Sudirman Djosetiko; Sri Untari (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2026)
This article examines the transformation and contemporary relevance of the Javanese Political Ethos (Etos Politik Jawa) within the multicultural political context of Suriname. In the classical Javanese tradition, political legitimacy is grounded not in formal authority but in moral integrity, self-restraint, and the maintenance of social harmony. Using a qualitative approach based on historical-philosophical analysis of classical Javanese texts and participatory observation within Javanese cultural and political circles in Suriname, this study analyzes how the ethos is maintained and reinterpreted in a diasporic setting. The findings show that the Javanese Political Ethos continues to function as a lived cultural practice, although in contemporary politics it is increasingly reduced to symbolic identity representation, critically referred to as “Bakmi and Nasi Goreng Politics.” Despite this transformation, the ethos retains normative relevance as a framework for ethical leadership and social cohesion in a pluralistic democracy. This study contributes to political culture and diaspora studies by demonstrating how normative traditions adapt while preserving their moral significance.